Growth and survival of young turbot (Scophthalmus maximus L.) produced with cryopreserved sperm - Chereguini-Fernández-Maquieira; María del Olvido; García-de-la-Banda, Inés; Rasines, Inmaculada; Fernández-Lamas, José Ángel (Aquaculture Research, 2002)
This study assessed the growth and survival over a year of two groups of 4-month-old turbot Scophthalmus maximus (L.) derived from artificial fertilization with fresh (FG) and cryopreserved sperm (CG). Growth in both groups, measured monthly in terms of length and weight, were compared. Survival was also recorded. No significant differences were found when we compared weight and length data in both groups. Growth rates were similar between FG and CG young turbot during 1 year. Likewise, the same survival rate (92.2%) was found in both groups. Our results show the good survival and growth of young turbot obtained from cryopreserved sperm, and confirm the cryopreservation technique as a useful tool for raising turbot for commercial purposes. Sí